The sediment distribution characteristics and transport pattern in the eastern China seas. (20th August 2022) - Mi, Beibei; Zhang, Yong; Mei, Xi
Abstract: As one of the most important margin seas around the west Pacific, the eastern China seas are important sink for terrigenous materials and forms multiple geology structures. So research the composition and spatial distribution of sediments could help us to understand the dynamics mechanism of the marine sedimentary environment, further to comprehend the land-sea interaction process. Based on high spatial resolution sediment survey in the eastern China seas, the distribution diagram of the sediment types was compiled to reveal the space regularities of sediment. In this study, the Principal Component Analysis (PCA) method was used to identify the controlling factors that are the main controls of the sediment distribution in the study area, which revealed three factors (F1, F2 and –F1) representing grain size categories of >5.75φ, 4.25–5.75φ and 1.50–3.00φ, respectively. F1 represents fine sediments (>5.75φ), -F1 represents coarse sediments (1.50–3.00φ), and F2 represents intermediate-sized sediments (4.25–5.75φ). The sediment transport patterns of the different grain size categories in the eastern China seas are discussed in the context of a comprehensive analysis of sediment grain size composition, material sources, flow patterns, and other factors. The results show that fine-grained sediments represent a "distant" sink of terrigenous material that formed in a stable and low-energy sedimentary environment. The coarse sediment deposits were formed in the late Pleistocene when the hydrodynamic conditions were relatively strong, and the intermediate-sized sediments were distributed in an area with a high concentration of suspension representative of mid-strength hydrodynamic conditions. Graphical abstract: Image 1